High prevalence of malignant ventricular arrhythmias in patients with early-stage left ventricular noncompaction. (3rd October 2022) - Sivilotti, F; Villatore, A; Berg, J; Romano, S C; Parciante, A; Pili, G; Fioravanti, F; El Sawaf, B; Sala, S; Della Bella, P; Peretto, G
Abstract: Background: Early-stage left ventricular non compaction (LVNC) is a nonischemic cardiomyopathy characterized with nondilated phenotype and unpredictable risk of malignant ventricular arrhythmias (MVA). Purpose: To report the occurrence of MVA in patients with early-stage LVNC. Methods: Consecutive patients (n=63) diagnosed with LVNC according to recognized criteria either on transthoracic echocardiogram or cardiac magnetic resonance were retrospectively enrolled. Patients with late-stage LVNC, defined by a coexistent dilated cardiomyopathy phenotype, were excluded (n=49). Patient-tailored medical treatment, as well as ICD implantation strategies, were based on the updated ESC guidelines integrated by the experience of a referral center for arrhythmia management. The study endpoint was the occurrence of MVA (defined as sustained VT, VF, or appropriate ICD therapy) by 5-year follow-up. Results: The study cohort consisted of 14 patients (mean age 37±17 y, 64% males), presenting with palpitation (n=4), syncope (n=4), or dyspnea on effort (n=6). LVNC was diagnosed by echocardiogram and cardiac magnetic resonance in 13 and 1 patients, respectively. Because of nonmalignant VA, seven patients (50%) underwent ICD implant before discharge. By 5-year follow-up, 5 patients (36%) experienced MVA, including VF or appropriate ICD shocks for fast VT. Left ventricular ejection fraction (LVEF) ≥45% was the only factor associated with the occurrence of MVA (5/11 event in cases with LVEF ≥45% vs. 0/3 events in controls with LVEF <45%; p=0.145). Baseline features, including age, gender, NC/C ratio, and clinical presentation were comparable between cases with LVEF ≥45% and controls, all p>0.05. Drug treatment, including RAAS inhibitors, betablockers and antiarrhythmics was also comparable. Conclusions: Our preliminary data show that in early-stage LVNC the occurrence of MVA is higher for patients with LVEF ≥45%. Efforts are needed to identify earlier predictors of arrhythmic risk, to improve patient selection for ICD implant. Funding Acknowledgement: Type of funding sources: None.